Almost popular [videorecording (DVD)] - Duffy-Little, Pamela; Rivera, Eleni; Turner, Ruby Rose; Miller, Reid; Ferreira, Isabella; Carpenter, Ellodee (Filmhub, 2025)
Susie and Bobbie, high school juniors, go on a quest to fulfill their dream of becoming part of the elite POP Girls who rule the school. After a series of unfortunate and humiliating attempts, they learn what matters.